Brand Image Effect on Selecting Place of Dentures Fabrication at Integrated Specialist Clinic of RSGM FKG UNAIR - Ria Nila Bawati; Stefanus Supriyanto; Sri Widati (Humanistic Network for Science and Technology (HNST), 2018)
Integrated Specialist Clinic of Oral and Dental Hospital, Faculty of Dentistry, Airlangga University (RSGM FKG UNAIR) provides oral and dental health care service ranging from basic medical level up to sub-specialistic covering 8 dental health fields. Based on data from 2012 to 2015, the highest number of patients is permanent tooth extraction patients. The large number of permanent tooth extraction patients is not followed by a large number of patients who return to install denture. The percentage of patience who returns to install the denture is only 24.67% of all permanent tooth extraction patients. The purpose of this study was to determine the effect of brand image factors on the selection of denture making site. The type of this research was analytic observational by using cross sectional approach. The research data was taken during September and October 2017 at place and time mutually agreed between researcher and respondent. The population of this research was permanent tooth extraction patients in Integrated Specialist Clinic RSGM FKG UNAIR in 2016. The sample size was 60 patients. Brand image based on the composite value of types of brand association of Integrated Specialist Clinic of RSGM FKG NAIR has an effect on the selection of denture making site. Keywords: Brand image, denture, Integrated specialist clinic, Permanent tooth extraction